Utilizações de informações genômicas para o melhoramento genético de características de crescimento em bovinos da raça Nelore - Terakado, Ana Paula Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Growth traits are fundamental to the genetic improvement of beef cattle, because they are directly related to the economy of the system. Recent technological advances have enabled the use of genomic data in the assessment of animals. The objective of this study was to evaluate models to predict breeding values from genomic data, and detection of DNA polymorphisms associated with growth traits in Nellore animals. Thus, it was genotyped 5,064 animals, using high-density SNPs Illumina Bovine HD assay (Illumina, San Diego, CA, USA), and after quality control 412,993 SNPs were used. In Chapter 2, three models were used to estimate the effects of markers for birth weight (BW), weight gains from birth to weaning (WGBW) and from weaning to yearling (WGWY), yearling height (YH) and cow weight (CW): better linear estimator not biased (GBLUP), BAYESCπ and Improved Bayesian least absolut shrinkage and selection operator (IBLASSO). Breeding values were desregressed and used as pseudo-phenotypes. Bayesian methods were the most suitable for estimating the effects of SNPs and genomic values for the studied traits. In Chapter 3, we applied the ssGBLUP model to estimate the effects of markers and associate them with BW, WGBW, WGWY, YH and CW. There were associations with BW in BTA (Bos taurus chromosomes) 14, with WGBW in BTA 5 and 29, with WGWY in BTA 11 and YH in BTA 8, distinguishing the genes TMEM68 (transmembrane protein 8B) associated with BW and YH, XKR4(XK, Kell blood group complex subunit-related family, member 4) associated with BW and NPR2 (natriuretic peptide receptor B) associated with the YH

As características de crescimento são fundamentais ao melhoramento genético de bovinos de corte, pois estão diretamente relacionadas à economia do sistema. Recentes avanços tecnológicos possibilitaram a utilização de dados genômicos na avaliação de animais de produção. Objetivou-se com este estudo avaliar modelos para predição de valores genéticos a partir de dados genômicos, bem como a detecção de polimorfismos de DNA associados à características de crescimento de animais da raça Nelore. Para tanto, foram genotipadas 5.064 animais, utilizando-se SNPs de alta densidade Illumina Bovine HD assay (Illumina, SanDiego, CA, USA) e, após o controle de qualidade, foram utilizados 412.993 SNPs. No Capítulo 2, foram utilizados três modelos para estimação dos efeitos dos marcadores para as características de peso ao nascer (PN), ganhos em peso do nascimento à desmama (GND) e da desmama ao sobreano (GDS), altura ao sobreano (ALTS) e peso da vaca (PV): melhor estimador linear não viesado (GBLUP), BAYESCπ e Improved Bayesian least absolut shrinkage and selection operator (IBLASSO). Foram utilizados os valores genéticos desregredidos como pseudo-fenótipos. Os métodos Bayesianos foram os mais adequados para estimação dos efeitos dos SNPs e dos valores genômicos para as características estudadas. No Capítulo 3, aplicou-se o modelo ssGBLUP para estimar os efeitos de marcadores e associá-los às características PN, GND, GDS, ALTS e PV. Observaram-se associações com PN no BTA (Bos taurus chromosomes) 14, com GND nos BTA 5 e 29, com GDS no BTA 11 e com ALTS no BTA 8, sendo destacados os genes TMEM68 (transmembrane protein 8B) associado ao PN e ALTS, XKR4(XK, Kell blood group complex subunit-related family, member 4) associado ao PN e NPR2 (natriuretic peptide receptor B) associado a ALTS
Keywords: Bovino de corte; Nelore (Zebu); Bovino - Crescimento; Genômica; Bovino - Melhoramento genetico; Genetica animal; Genomics